2021
DOI: 10.1002/ijop.12798
|View full text |Cite
|
Sign up to set email alerts
|

Resource loss and mental health during COVID‐19: Psychosocial protective factors among U.S. older adults and those with chronic disease

Abstract: Across the globe, COVID‐19 has disproportionately affected the physical and mental health of several vulnerable groups. In a series of two cross‐sectional studies conducted April to July 2020, we examined its acute mental health effects on two vulnerable U.S. community samples—home‐bound older adults who were at or below the poverty line (Study 1, N = 293, M age = 76.94, SD = 8.64; 75.1% female, 67.9% Black) and adults with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…Our findings add to recent observations on the relevance of strong prior social networks, as well as current social support and mindfulness for protection of mental health during the COVID-19 pandemic period [ 16 , 17 ]. Consistent with other work, which found psychosocial characteristics such as personal mastery and other resource measures negatively correlated with pandemic related psychological burden in all adults [ 18 ], vulnerable adults [ 19 ], and older adults [ 20 ], BLSA participants with more personal resources including awareness of their need for social support and high personal mastery tended to report pandemic impacts incorporating positive perspectives.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings add to recent observations on the relevance of strong prior social networks, as well as current social support and mindfulness for protection of mental health during the COVID-19 pandemic period [ 16 , 17 ]. Consistent with other work, which found psychosocial characteristics such as personal mastery and other resource measures negatively correlated with pandemic related psychological burden in all adults [ 18 ], vulnerable adults [ 19 ], and older adults [ 20 ], BLSA participants with more personal resources including awareness of their need for social support and high personal mastery tended to report pandemic impacts incorporating positive perspectives.…”
Section: Discussionsupporting
confidence: 84%
“…Resilience was experienced as a person-by-context interaction from a United States perspective ( Herbers et al, 2021 ), thus highlighting that the context and the environment are detrimental in an individual’s display or activation of resilience. A United States study also showed that optimism and resilience as traits were beneficial, as these characteristics buffered the impact of loss of resources on mental health in the elderly and chronically ill people ( McElroy-Heltzel et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, awareness of perceived silver linings, particularly those related to social cohesion, safety and security and others influencing perceived agency are important to incorporate and prioritise into public health strategies as the country responds to the evolving pandemic. People with chronic disease are more vulnerable to mental health issues and there is a growing body of literature on mental illness in people with chronic disease during the pandemic [33,34].…”
Section: Discussionmentioning
confidence: 99%